Epidemiology and Treatment of Hepatitis C Genotypes 5 and 6 - Khalid Al Naamani; Siham Al Sinani; Marc Deschênes (Canadian Journal of Gastroenterology)
Chronic hepatitis C infection is a major global health problem. The WHO estimates the number of infected people worldwide to be approximately 170 million. The estimated number of hepatitis C virus (HCV)-infected people in Canada is approximately 250,000, with approximately 5000 Canadians newly infected each year. Based on the identification of genomic differences, HCV has been classified into six genotypes; genotype may influence the outcome of antiviral therapy. HCV genotypes 1, 2 and 3 are widely distributed throughout the world and have been the focus of the majority of epidemiological, natural course and treatment studies. Although HCV genotypes 5 and 6 are prevalent in certain geographical areas, they are studied less extensively. HCV genotypes 5 and 6 are uncommon in Canada and account for less than 5% of HCV-infected Canadians. However, immigration and travel can alter the epidemiology of these uncommon genotypes. The present article reviews and summarizes the available data regarding the epidemiology and treatment of HCV genotypes 5 and 6. Genotype 5 is endemic in the northern part of South Africa while genotype 6 is reported primarily in Asia. Available data show that 48 weeks of treatment with a combination of pegylated interferon and ribavirin lead to a higher sustained virological response compared with HCV genotypes 1 and 4. None of the approved direct-acting antiviral agents is currently recommended for the treatment of HCV genotypes 5 or 6.